Synergistic effects of Rhizobium, Bacillus and Arbuscular Mycorrhizal fungi on enhancing cotton growth - Tasleem Sultana; Pavan Kumar Pindi (Iranian Journal of Microbiology)
Background and Objectives: Telangana district is renowned for its prominence in cotton production, a crop vital to the livelihoods of local farmers. For years, synthetic fertilizers have been relied upon to bolster yields, but escalating costs have shifted focus towards biofertilizers as a cost-effective and sustainable alternative. Materials and Methods: A microbial consortium comprising Rhizobium sp. PKS, Bacillus sp. PU-7, and Funneliformis mosseae AMF was employed. Microbial identification was performed using 16S rRNA gene sequencing. Biochemical evaluations of consortium-inoculated plants included measurements of protein, sugar, proline, and chlorophyll levels, along with IAA quantification. Results: A consortium of Bacillus sp. PU-7, Rhizobium sp. Pks [NCBI OK663003, NCMR-MCC4960], and Funneliformis mosseae enhanced Mahyco cultivar growth. Treatment increased plant height, fresh and dry weight, and improved biochemical profiles (reduced proline, elevated IAA, protein, chlorophyll, and sugars). Soil field trials were undertaken in four cotton-producing regions of Mahabubnagar region confirmed for efficacy, with deep black soil promoting phytohormone synthesis (IAA-917.66 ± 2.51) and light black soil (IAA- 802 ± 2) enhancing plant growth. Conclusion: Given these outcomes, the application of the tested bioinoculants and AMF spores is suggested as an effective strategy to enhance cotton development and yield in the soils of Mahabubnagar, potentially revolutionizing the district's agricultural practices.